A combined valve-sparing aortic root replacement and primary tetralogy of Fallot repair in an unoperated adult: a case report - Xuping Feng; Dou Yuan; Juan Wu; Yongjun Qian (Frontiers in Cardiovascular Medicine, 2026)
Background Progressive aortic root dilation represents a life-threatening sequela of uncorrected tetralogy of Fallot (TOF), predisposing patients to aortic regurgitation, dissection, and rupture. Valve-sparing aortic root replacement (VSARR) offers an attractive alternative to mechanical valve replacement by eliminating prosthesis-related complications and lifelong anticoagulation. However, experience with VSARR in unoperated adult TOF patients remains exceptionally limited. Case presentation We report a 35-year-old male with unrepaired TOF who presented with progressive exertional dyspnea, cyanosis, and atrial fibrillation. Comprehensive imaging revealed severe aortic root dilation (55.4 mm), moderate-to-severe aortic regurgitation, perimembranous ventricular septal defect, infundibular stenosis, and secundum atrial septal defect. We performed single-stage surgical correction comprising ventricular septal defect closure, infundibular resection, pulmonary valvotomy with transannular patch, atrial septal defect closure with fenestration, and Yacoub remodeling VSARR. The patient tolerated the 208-min cardiopulmonary bypass procedure well, with immediate postoperative echocardiography demonstrating trivial aortic regurgitation. He was discharged on postoperative day 7 in sinus rhythm without complications. Conclusions This case demonstrates the feasibility of combining Yacoub VSARR with primary intracardiac TOF repair in unoperated adults. The procedure successfully preserved native aortic valve function while correcting congenital anatomy, avoiding prosthetic valve-related morbidity. This approach may expand surgical options for adults with TOF-associated aortopathy, though long-term durability data are needed.